STUDY OF THE INTERRELATON BETWEEN KNOWLEDGE OF PSYCHOLOGICAL SELF-REGULATION METHODS OF THE PERSON AND MINDFULNESS (EXAMPLE OF TEACHERS) - Gevorgyan, Astghik; Poghosyan, Sona (Modern Psychology, 2024)
The purpose of this article is to study the importance of psychological self-regulation among teachers, as well as their level of mindfulness. Survey, testing and content analysis methods were applied. We applied localized version of Five Facet Mindfulness Questionnaire and Mindfulness experience questionnaire. In the article, we present the responses or coping mechanisms to stressful situations given by the teachers. Based on the teachers' answers, we have distinguished adaptive and non-adaptive coping mechanisms. Referring to the methods of psychological self-regulation, we presented the role of psychological self-regulation and particularly mindfulness meditation in the process of overcoming stress. During the experimental research, we tried to find out how teachers' knowledge and application of psychological self-regulation methods interrelates with mindfulness.As a result of the research we conclude that psychological self-regulation, especially mindfulness meditation, is not widespread among teachers, moreover, there is no clear understanding of self-regulation methods, their use and importance. The level of mindfulness among teachers is average.
Keywords: self-regulations; stress; mindfulness; coping mechanisms; adaptive; maladaptive; teacher; education